Authoritative Sources of Qur’anic Interpretation in the Tafsir Study Community of the Batak Angkola Society - Hasiah Hasiah; Nurus Shalihin; Novizal Wendry; Desri Ari Enghariano; Sufrin Efendi Lubis (Jurnal Ushuluddin, 2025)
This study examines the authoritative sources utilized by the Tafsir study community within the Batak Angkola society in Padangsidimpuan City for interpreting the verses of the Qur’an. The objective is to identify and analyze the primary references employed by this community to understand and convey Qur’anic interpretations. A qualitative research method with an ethnographic approach was used. Data were collected through participatory observation, in-depth interviews, and a literature review relevant to the study. The findings reveal that the Tafsir study community relies on a combination of classical and modern tafsir as their main sources for Qur’anic interpretation. Additionally, local culture influences distinctive interpretive patterns among the Batak Angkola society, although some community members face challenges in integrating local cultural elements into their interpretations. The study concludes that the authoritative sources used by the Tafsir community reflect a dynamic adaptation between Islamic teachings and local culture; however, not all members incorporate local culture into their interpretations. Ultimately, this interpretive study produces a unique and contextual approach to Qur’anic exegesis.